2012
DOI: 10.1186/2045-8118-9-20
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging in elderly patients with idiopathic normal pressure hydrocephalus or Parkinson’s disease: diagnosis of gait abnormalities

Abstract: BackgroundGait abnormalities in the elderly, characterized by short steps and frozen gait, can be caused by several diseases, including idiopathic normal pressure hydrocephalus (INPH), and Parkinson’s disease (PD). We analyzed the relationship between these two conditions and their association with gait abnormalities using laboratory test data and findings from diffusion tensor imaging (DTI).MethodsThe study involved 10 patients with INPH, 18 with PD, and 10 healthy individuals (control group). Fractional anis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 38 publications
0
53
0
1
Order By: Relevance
“…9,16,41,45,48,55,57,59,75,84,94,125 Understanding the periventricular white matter tracts is helpful not only in defining more precise surgical strategies, but also in clarifying the symptoms of and appropriate treatment for patients with hydrocephalus and periventricular lesions. 11,18,36,38,40,47,50,52,58,65,66,76,80,101 This study examines the tracts at risk in the 3 surgical routes-anterior, posterior, and lateral-to the lateral ventricle. The anterior approaches include the anterior interhemispheric transcallosal, anterior frontal transcortical, and anterior frontal interhemispheric transrostral; the posterior approaches include the posterior transcortical (superior parietal lobule), posterior interhemispheric transcallosal, posterior interhemispheric precuneal, supracere- …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…9,16,41,45,48,55,57,59,75,84,94,125 Understanding the periventricular white matter tracts is helpful not only in defining more precise surgical strategies, but also in clarifying the symptoms of and appropriate treatment for patients with hydrocephalus and periventricular lesions. 11,18,36,38,40,47,50,52,58,65,66,76,80,101 This study examines the tracts at risk in the 3 surgical routes-anterior, posterior, and lateral-to the lateral ventricle. The anterior approaches include the anterior interhemispheric transcallosal, anterior frontal transcortical, and anterior frontal interhemispheric transrostral; the posterior approaches include the posterior transcortical (superior parietal lobule), posterior interhemispheric transcallosal, posterior interhemispheric precuneal, supracere- …”
Section: Discussionmentioning
confidence: 99%
“…40,47,66,80 Recent studies have reported lower FA in NPH than in AD or PD in the corpus callosum. 65,66 Mataró et al and Hoza et al showed a negative correlation between the size of the frontal fibers of the corpus callosum and mild impairment of attention and executive function in idiopathic NPH.…”
Section: 58mentioning
confidence: 99%
See 2 more Smart Citations
“…24 Marumoto and others investigated FA in 5 different brain regions in 10 iNPH patients, 18 PD patients, and 10 healthy controls. 37 According to this study, FA in the anterior thalamic radiation and the minor forceps was lower in iNPH patients than in the PD patients. Moreover, FA in the anterior thalamic radiation was statistically significantly associated with gait disturbances in both patient groups.…”
mentioning
confidence: 99%